(untitled) (Bangladesh Journal of Agricultural Research, 2019)
Damping-off (Pythium aphanidermatum) is a soil-borne disease which accounts for seedling mortality and significant yield losses in tomato production. Laboratory and screenhouse experiments were conducted in 2017, with a repeated field trial in 2018 to evaluate the efficacy of combining three biological control agents (BCAs), Trichodermaviride, T. harzianumand Bacillus subtilis with Allium sativumextract for the integrated management of the disease in tomato crop. Treatments were laid out in a completely randomized design and randomized complete block design in the screenhouse and field experiments, respectively with eighteen treatments and three replications. The BCAs and extract were formulated and applied using seed treatment and soil sprinkling methods. Treatment combinations of BCAs with A. sativumwere more effective in the reduction of mycelial growth of the pathogen with inhibitory values that ranged between 77.6-91.2% than single inoculation. Seed treatment before planting was more effective than soil sprinkle method, reducing pre-emergence and damping-off incidence to between 6.8-18.3% and 9.7-26.3% under screenhouse and field conditions, respectively than the sprinkling method. Soil sprinkle with T. harzianumin combination with A. sativumextract had the highest cumulative tomato fruit yield of 902 kg/ha-1under field conditions. This study showed that combined application of BCAs and A. sativumextract reduced damping-off disease and thereby improved the fruit yield of tomato. Bangladesh J. Agril. Res. 44(3): 553-567, September 2019